(untitled) (Medical Forum Monthly, 2024)
Objective: To analyze the role of educational updates for pediatrician, general physicians and health care providers in management of undescended testis. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Department of Pediatric Surgery at Nishtar hospital, Multan, from June 2023 to May 2024. Methods: The study included all pediatricians, general physicians, and health care providers working in the Department of Pediatric Surgery. Doctors working in other hospital departments were excluded. The institutional review board approved the study. A survey tool introduced by Lim et al in Singapore was used to assess healthcare providers' awareness regarding managing undescended testis. The tool comprised short answers and multiple-choice questions focused on managing undescended testis. Results: Of the 120 participants, 61 (50.8%) knew about the incidence of undescended testis, 68 (56.7%) knew about the age to check gonads position, 68 (56.7%) check for physical features of a patient having undescended testis, 84 (70.0%) know about the recommended treatment of U.D, 31 (25.8%) know about the best timing of referral to a surgeon, 50 (41.7%) know about the recommended timing of surgery. Conclusion: The management of undescended testis (UDT) can be significantly enhanced through targeted educational updates for pediatricians, general physicians, and other healthcare providers. Improved knowledge and awareness regarding the timely diagnosis, referral, and treatment of UDT are important to reducing the risk of long-term complications.